Sperm DNA fragmentation in infertile men with genitourinary infection by Chlamydia trachomatis and Mycoplasma - Gallegos, Guadalupe; Ramos, Benito; Santiso, Rebeca; Goyanes, Vicente; Gosálvez, Jaime; Fernández, José Luis (Fertility and sterility, 2008)
To determine the frequency of sperm cells with fragmented DNA in semen samples from men with genitourinary infection by Chlamydia trachomatis and Mycoplasma and the influence of antibiotic therapy, using the sperm chromatin dispersion test with the Halosperm kit. Prospective study. University-affiliated reproductive medicine center, medical genetics laboratory, and academic biology center. One hundred forty-three male member of couples attending the andrology infertility center and a group of 50 fertile subjects. The effect of antibiotic treatment was evaluated in 95 male patients. None. Classical semen analysis (concentration, motility, morphology, and vitality), sperm DNA fragmentation, and clinical outcome. The mean percentage of sperm cells with fragmented DNA was 35.2% +/- 13.5%, 3.2 times higher than in the control fertile group (10.8% +/- 5.6%). Concentration, morphology, and motility were also significantly affected but to a much lower degree. Sperm vitality was not significantly affected. After 3.8 +/- 2.2 months of antibiotic treatment, the mean frequency of spermatozoa with fragmented DNA decreased from 37.7% +/- 13.6% to 24.2% +/- 11.2%. Sperm concentration and motility were not significantly improved. In a group of 16 couples who attempted pregnancy during antibiotic treatment course, only 12.5% achieved pregnancy. However, in a group of 14 couples who attempted pregnancy after finishing the antibiotic treatment, 85.7% achieved it. The only significant differences found between groups was the rate of sperm DNA fragmentation and morphology. Patients with genitourinary infection by Chlamydia trachomatis and Mycoplasma have increased sperm DNA fragmentation in comparison with fertile controls. This increase is proportionally greater than the influence on classical semen parameters and could result in a decreased fertility potential. Antibiotic therapy appears to be important in providing a remedy for infection-induced high DNA fragmentation levels.